To assess the knowledge, attitude and practices of people regarding overweight and obesity: a cross-sectional study - Jajulwar, Mahesh B.; Meshram, Pawan V.; Saji, Daniel A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Prevention and management of obesity is largely depends on motivation and education of people about obesity, in turn this can be greatly facilitated by adequate baseline data on the knowledge, attitude and practise (KAP) of people. The aim of this study was to assess the KAP on obesity among obese people of an urban slum of Mumbai. Methods: A cross-sectional study was conducted in randomly selected sample from Shivaji Nagar urban slum area of Mumbai. Structured questionnaire were used to test their knowledge, attitude and practises regarding obesity. Results: 350 adults of age more than 18 years were analysed. 56% were male and 81.1% were of Muslim community. Prevalence of obesity and overweight was found to be 8.6% and 32.3% respectively as per body mass index (BMI). 42.0% subject’s thought that they are slim, 43.4% thought that they are fit and only 14.6% subjects considered hat they have weight more than normal. Only 46.9% said that they are frequently teased about their weight or physical appearance and only 28.6% said that teasing affected them mentally. 70.9% subjects know that there are health consequences of being obese and only 7.7% have made any effort to reduce weight. 88.3% subjects think diet control and 79.3% think exercise and 11.7% consider medication as a treatment modality for obesity. Conclusions: There appears to be lack of knowledge about obesity and its effects on health, as well as the methods for reducing weight. An IEC program can be developed in this context.